Does favorable tax-treatment of housing reduce equipment investment? - Broadbent, Ben; Kremer, Michael 1964- (1997)
It is often argued that low tax rates on owner-occupied housing divert investment from equipment. This paper demonstrates that if people are heterogeneous in their propensity to save, and if there are constraints on borrowing, favorable tax treatment of owner-occupied housing up to a certain value increases equipment investment. This is because low housing taxes encourage renters to become owner-occupiers, and this leads existing owner-occupiers to shift their portfolio of other assets from rental housing to equipment.
Keywords: Steuer; Ökonometrisches Modell; Home ownership -- Econometric models; Housing -- Taxation -- Econometric models; Industrial equipment -- Econometric models; Saving and investment -- Econometric models